Innovative hybrid laminates of aluminium alloy foils and fibre‐reinforced thermoplastic layers: Innovative hybride Laminate aus Aluminiumlegierungsfolien und faserverstärkten thermoplastischen Schichten. Issue 11 (16th November 2016) - Nestler, D.; Trautmann, M.; Nendel, S.; Wagner, G.; Kroll, L.
Abstract : The article is about the consolidation of semi‐finished products from fibre‐reinforced polyamide layers and aluminium alloy foils to produce hybrid laminates. In addition it also focuses on the suitable interface engineering between fibre‐reinforced plastics and metal foils, as well as the resulting mechanical properties. The mechanical, chemical and physical surface treatment methods, as well as the adhesive layers for the material combination of carbon fibre‐reinforced polyamide 6 and the aluminium alloy EN AW‐6082 T4 are examined at the thermally bonded overlapping joints and subsequently evaluated regarding the possible in‐line integration in a large‐scale production. The mechanical properties of various hybrid laminates with a varied fibre‐reinforced structure are compared to each other. The mechanical properties of the hybrid material system can be improved by the addition of extra layers of polyamide 6 and glass fibre‐reinforced polyamide 6, which in turn also add a gradient of the material to the boundary surface between the aluminium and the carbon fibre‐reinforced plastic.